ANALISIS PERKEMBANGAN TEKNOLOGI INTERNET OF THINGS (IOT) DALAM MONITORING KESEHATAN PASIEN DI RUMAH SAKIT - Michella Valery; Calista Silvia Jaya; Daniel Mido Setiawan; Dorie Pandora Kesuma (CV. Denasya Smart Publisher, 2026)
The development of information and communication technology has encouraged the implementation of the Internet of Things (IoT) in the healthcare sector, particularly for patient monitoring in hospitals. Manual monitoring processes often experience delays in information delivery, dependence on medical personnel, and the risk of human error. This study aims to analyze the development of IoT technology in patient health monitoring, its benefits, and the challenges faced in its implementation. The research employed a qualitative method using a literature review approach through the collection and analysis of various journals, books, and scientific articles related to IoT in healthcare. The results indicate that IoT enables real-time patient monitoring through internet-connected sensors, allowing healthcare professionals to access patient data quickly and efficiently. In addition, IoT has been integrated with cloud computing and artificial intelligence technologies to improve data management efficiency. Despite offering numerous benefits, its implementation still faces challenges related to data security, infrastructure requirements, implementation costs, and human resource readiness. Therefore, IoT has significant potential to improve the quality of healthcare services in hospitals.